Inequities and Quality of Life in Argentina Geography and Quality of Life in Argentina - Celemin, Juan Pablo; Velázquez, Guillermo (The Latin American Studies Book Series, 2022)
XVIII, 353 p. 179 illus., 172 illus. in color.